Kinematics of thorax and pelvis during maximal accelerated sprinting - Nagahara, R.; Matsubayashi, T.; Matsuo, A.; Zushi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Changes in thorax and pelvis movements during acceleration phase of maximal sprinting, which relate to acceleration ability, are still unknown. This study aimed to clarify the changes in thorax and pelvis movements during maximal accelerated sprinting and its relation to better acceleration ability. Twelve sprinters performed a 60-m sprint, during which 3D kinematics of the sprinters were obtained. The same patterns of motions were maintained for thorax and pelvis respectively throughout the entire acceleration phase, although phase profiles of relative movements between thorax and pelvis in three planes differed. Moreover, results indicated that effective acceleration is characterised by suppressed trunk bend, delayed trunk rotation, and forward tilted pelvis in the middle acceleration section and suppressed trunk bend in the final acceleration section.